Combining Microstrip Meander Line and Dipole Antennas: Dual-Band Solution for PIR Equipment - Muhamad Adimukti Prasojo; Muh Wildan; Eriyandi; Wibowo, Priyo (Emitor: Jurnal Teknik Elektro, 2024)
One of the aviation navigation tools is the Instrument Landing System (ILS), which functions to provide guidance signals to aircraft in the final approach position toward the runway. The ILS consists of three components: the Localizer, Glide Path, and Marker Beacon. To ensure aviation safety and security, navigation equipment must be regularly inspected through Ground Inspection. With current technological advancements, Ground Inspection is being conducted using UAVs or drones. One of the components to be installed on the UAV is the PIR, which requires two antennas of different lengths to receive signals from the Localizer and Glide Path.In this study, a dual-band antenna was developed that combines a dipole antenna and a meander line microstrip antenna for frequencies 108-112 MHz and 328.6-335.4 MHz, using CST Studio Suite 2021 software and FR-4 substrate material. Simulation results showed good performance with a return loss value of -19.43471 dB, VSWR of 1.238951, and a bandwidth of 2 MHz at a frequency of 110.5 MHz, and a return loss value of -27.41626 dB, VSWR of 1.119686, and a bandwidth of 2.5 MHz at a frequency of 329.6 MHz.Measurement parameter values for the VHF band were a return loss of -14.1680 dB, VSWR of 1.487, and a bandwidth of 14.6 MHz. Meanwhile, for the UHF band, there was a shift in the resonance frequency to 368.5 MHz with a return loss value of -15.4202 dB, VSWR of 1.408, and a bandwidth of 11.4 MHz. In this antenna design, a dual-band combination of a dipole and a meander line microstrip antenna with dimensions of 320 mm was achieved, capable of operating in both the VHF and UHF frequency bands simultaneously. However, this antenna can only operate at the Localizer working frequency.